«Business angels» investment as a special form of business financing - Shuba, Marina; Shuba, Olena (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
Taking into account the growing need to expand and diversify the forms of business financing in Ukraine, especially in the early stages, it is necessary to pay more attention to the study of business angels investment. For the success of the start-up, at least there should be an original idea with a development perspective, the owner of this ingenious idea and investors, which may be business angels. In this regard, the activities of business angels are interesting for study and research. The subject of research of the article is “angelic” investments as a special form of business financing. The goal is to explore the essence and to analyze the peculiarities and trends of business angels investment as a special form of business financing. The objective is to research peculiarities and current state of business angels investments in Europe and in Ukraine. Methods: system analysis is used to determine the peculiarities of development of business angels investment in European countries; trend analysis– to predict future total of business angels active in early-stage investments in Europe. The following results were obtained: classification of business angels by different scientists were provided; the main areas of early stage investment in Europe, dynamics of business angels investment, number of business angels in Europe were analized; the main problems faced by Ukrainian angels and trends of business angels investment in Ukraine were systematized. Conclusions: the analysis of the peculiarities and trends of business angels investment as a special form of business financing in Europe can be efficiently used in early stage investment as recommendations for using non-traditional sources of financing in Ukraine.